High-mobility group box 1 is an important mediator of microglial activation induced by cortical spreading depression. Issue 3 (March 2017) - Takizawa, Tsubasa; Shibata, Mamoru; Kayama, Yohei; Shimizu, Toshihiko; Toriumi, Haruki; Ebine, Taeko; Unekawa, Miyuki; Koh, Anri; Yoshimura, Akihiko; Suzuki, Norihiro
Single episodes of cortical spreading depression (CSD) are believed to cause typical migraine aura, whereas clusters of spreading depolarizations have been observed in cerebral ischemia and subarachnoid hemorrhage. We recently demonstrated that the release of high-mobility group box 1 (HMGB1) from cortical neurons after CSD in a rodent model is dependent on the number of CSD episodes, such that only multiple CSD episodes can induce significant HMGB1 release. Here, we report that only multiple CSD inductions caused microglial hypertrophy (activation) accompanied by a greater impact on the transcription activity of the HMGB1 receptor genes, TLR2 and TLR4, while the total number of cortical microglia was not affected. Both an HMGB1-neurtalizing antibody and the HMGB1 inhibitor glycyrrhizin abrogated multiple CSD-induced microglial hypertrophy. Moreover, multiple CSD inductions failed to induce microglial hypertrophy in TLR2/4 double knockout mice. These results strongly implicate the HMGB1–TLR2/4 axis in the activation of microglia following multiple CSD inductions. Increased expression of the lysosomal acid hydrolase cathepsin D was detected in activated microglia by immunostaining, suggesting that lysosomal phagocytic activity may be enhanced in multiple CSD-activated microglia.